PIC Simulations of Excited Waves in the Plasmoid Instability - Shahraki Pour, Mahdi; Hosseinpour, Mahboub (Frontiers in Astronomy and Space Sciences, 2022)
Fragmentation of an elongated current sheet into many reconnection X-points, and therefore multiple plasmoids, occurs frequently in the solar corona. This speeds up the release of solar magnetic energy in the form of thermal and kinetic energy. Moreover, due to the presence of multiple reconnection X-points, the particle acceleration is more efficient in terms of the number of accelerated particles. This type of instability called “plasmoid instability” is accompanied with the excitation of some electrostatic/electromagnetic waves. We carried out 2D particle-in-cell simulations of this instability in the collisionless regime, with the presence of non-uniform magnetic guide field to investigate the nature of excited waves. It is shown that the nature and properties of waves excited inside and outside the current sheet are different. While the outside perturbations are transient, the inside ones are long-lived, and are directly affected by the plasmoid instability process.